Some borrowers are more equal than others: Bank funding shocks and credit reallocation - Olivier De Jonghe; Hans Dewachter; Klaas Mulier; Steven Ongena; Glenn Schepens (National Bank of Belgium, 2018)
This paper provides evidence on the strategic lending decisions made by banks facing a negative funding shock. Using bank-firm level credit data, we show that banks reallocate credit within their loan portfolio in at least three different ways. First, banks reallocate to sectors where they have a high market share. Second, they also reallocate to sectors in which they are more specialized. Third, they reallocate credit towards low-risk firms. These reallocation effects are economically large. A standard deviation increase in sector market share, sector specialization or firm soundness reduces the transmission of the funding shock to credit supply by 22, 8 and 10 %, respectively.
Keywords: G01; G21; 330; Credit reallocation; bank funding shock; bank credit; sector market share; sector specialization; firm risk